2018
DOI: 10.1007/s00606-018-1543-y
|View full text |Cite
|
Sign up to set email alerts
|

Pollination biology and breeding system in five nocturnal species of Oenothera (Onagraceae): reproductive assurance and opportunities for outcrossing

Abstract: The capacity to produce seed, both by selfing and outcrossing, or mixed mating strategies, is considered a mechanism for overcoming unpredictable pollinator availability. In the present study, we investigate breeding system, insect visitations and the role of insect visitors in the pollination of five species of Oenothera subsect. Oenothera. Field experiments showed that autonomous selfing occurs at bud stage, prior to the opening of the flower. Control flowers showed similar seed set to hand-pollinated flower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…We recorded diurnal insect visitation on each flower for approximately 1 h using high-definition video cameras (Sony, San Diego, CA, USA) during pollinator activity (08:00-16:00 hours) on warm, sunny days, capturing a total of 130 h of film. We note that although many Oenothera species are visited by both diurnal and nocturnal floral visitors, the importance of these groups as pollinators varies across species (Rhodes et al, 2017;Antoń and Denisow, 2018;Krakos and Austin, 2021). Prior work has demonstrated that O. fruticosa is visited by diurnal pollinators including, butterflies, bees, and beetles, with no record of nocturnal visitors (Primack and Silander, 1975;Silander and Primack, 1978;Krakos and Austin, 2021).…”
Section: Study Species and Sitementioning
confidence: 93%
“…We recorded diurnal insect visitation on each flower for approximately 1 h using high-definition video cameras (Sony, San Diego, CA, USA) during pollinator activity (08:00-16:00 hours) on warm, sunny days, capturing a total of 130 h of film. We note that although many Oenothera species are visited by both diurnal and nocturnal floral visitors, the importance of these groups as pollinators varies across species (Rhodes et al, 2017;Antoń and Denisow, 2018;Krakos and Austin, 2021). Prior work has demonstrated that O. fruticosa is visited by diurnal pollinators including, butterflies, bees, and beetles, with no record of nocturnal visitors (Primack and Silander, 1975;Silander and Primack, 1978;Krakos and Austin, 2021).…”
Section: Study Species and Sitementioning
confidence: 93%
“…Studies in natural populations indicate wide variability in mating systems, but also show that mixed mating (self-and cross-pollination) are more common than expected [5,38,39]. The genus Oenothera is no exception, since wide variation is recognized in the species mating systems [7] and both cross-and self-pollination can occur in Onagraceae species that present, positive herkogamy [32]. Gallego-Fernández and García-Franco [34] noted positive herkogamy in O. drummondii, but it has not relationship with latitude increase.…”
Section: Mating System and Fruit And Seed Characteristics In Native Populationsmentioning
confidence: 99%
“…This indicates that, even though nonnative populations are isolated in geographically distant sites, they maintain a high level of self-compatibility and have not modified their potential for a mixed pollination system. This also suggests that these populations can take advantage of local pollinators [29,50], which could allow them to invade new sites [7]. Several Oenothera species have become successfully established in Europe and in other regions of the world, where some taxa are considered to be actively invasive species [7,44,51], similarities in environmental conditions between their native habitats and invaded sites must be important factors in the success of these species.…”
Section: Comparison Between Native and Non-native Populationsmentioning
confidence: 99%
See 2 more Smart Citations